Comparative study of file efficiency rotatories in cleaning simulated channels (ProTaper Next x X-Gray) (Research, Society and Development, 2022)
The cleaning and shaping of root canals are fundamental steps that directly influence the success of endodontic treatment. The aim of the study was to compare the modeling efficiency of ProTaper Next (Dentsply Maillefer, Ballaigues, Switzerland) and X-Gray (TDK, China) rotary files in simulated root canal instrumentation. Twenty acrylic blocks were used (IM do Brasil, São Paulo, Brazil), divided into two groups with ten acrylic blocks each, being, group 1 – PTN; group 2 - XG. The blocks were filled with black ink (Acrilex, China). Then, the simulated canals were patted on an acrylic block with a #10 K-file. Pre- and post-instrumentation images were obtained for further overlay and analytical comparison in Adobe PhotoShop CS5.1 imaging software (Adobe System, San José, USA). For statistical analysis, the Shapiro-Wilk and Mann Whitney tests were performed. Results: There were no significant differences when comparing PTN and XG. It is concluded that both the ProTaper Next and X-Gray instruments presented similar preparations in terms of conservation, modeling and transport of the canals.Keywords: Root canal; Endodontics; Rotary instruments.